(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article is devoted to the prospects of reforming the tax system in the context of globalization. It examines the scientific justification of the tax system and identifies systemic problems that hinder the dynamic economic growth of the Republic of Uzbekistan. The scientific analysis is carried out on the basis of studying the tax system and the share of each tax in the state budget revenues of the Republic of Uzbekistan, possible prospects for their solution and the current conditions for its development.